2019
DOI: 10.3389/fncel.2019.00547
|View full text |Cite
|
Sign up to set email alerts
|

Store-Operated Calcium Channels Are Involved in Spontaneous Slow Calcium Oscillations in Striatal Neurons

Abstract: The striatum plays an important role in linking cortical activity to basal ganglia output. Striatal neurons exhibit spontaneous slow Ca 2+ oscillations that result from Ca 2+ release from the endoplasmic reticulum (ER) induced by the mGluR5-IP3R signaling cascade. The maximum duration of a single oscillatory event is about 300 s. A major question arises as to how such a long-duration Ca 2+ elevation is maintained. Store-operated calcium channels (SOCCs) are one of the calcium (Ca 2+)-permeable ion channels. SO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The molecular composition of SOCs in MSNs has not been well established. Kikuta et al (2019) found strong expression of Orai2, moderate expression of Orai3, and sparse expression of Orai1 in striatal GABAergic neurons with strong expression of both STIM1 and STIM2. Interestingly, knockdown of STIM1, Orai1, or TRPC1 proteins leads to dramatic reduction of SOCE in MSNs (Vigont et al, 2015), indicating STIM1, Orai1, and TRPC1 mediate SOCE in MSNs.…”
Section: Socs In the Striatum Soc Components And Functions In Striatamentioning
confidence: 83%
See 2 more Smart Citations
“…The molecular composition of SOCs in MSNs has not been well established. Kikuta et al (2019) found strong expression of Orai2, moderate expression of Orai3, and sparse expression of Orai1 in striatal GABAergic neurons with strong expression of both STIM1 and STIM2. Interestingly, knockdown of STIM1, Orai1, or TRPC1 proteins leads to dramatic reduction of SOCE in MSNs (Vigont et al, 2015), indicating STIM1, Orai1, and TRPC1 mediate SOCE in MSNs.…”
Section: Socs In the Striatum Soc Components And Functions In Striatamentioning
confidence: 83%
“…Additionally, a recent study demonstrates that deletion of TRPC1 largely reduced SOCE in MSNs (Wu J. et al, 2018), further indicating an important role of TRPC1 in MSN SOCE. In addition, SKF96365, a SOC and TRPC channel inhibitor, was found to reduce the frequency of spontaneous slow Ca 2+ oscillations in these neurons, indicating the SOCE has a role in Ca 2+ signaling in MSNs (Kikuta et al, 2019).…”
Section: Socs In the Striatum Soc Components And Functions In Striatamentioning
confidence: 88%
See 1 more Smart Citation
“…As mentioned in the introduction, Mn 2+ is known to be a surrogate marker for Ca 2+ , hence AIM-MRI can measure changes in neural activity by evaluating the R1 map. However, we need to be aware that Mn 2+ can pass through not only VDCCs but also other Ca 2+ -permeable channels, such as some ligand-gated channels and store-operated calcium channels ( Uehara et al, 2002 ; Itoh et al, 2008 ; Tu et al, 2009 ; Chen et al, 2015 ; Bouabid et al, 2016 ; Kikuta et al, 2019 ). The inositol 1,4,5-trisphosphate receptor on the endoplasmic reticulum membrane is also permeable to Mn 2+ ( Striggow and Ehrlich, 1996 ).…”
Section: Discussionmentioning
confidence: 99%